"If You Have It, I Want It...Now!" the Effect of Envy and Construal Level on Increased Purchase Intentions - (:unkn) unknown (My University, 2014)
When a person wants something that another has, they often experience feelings of envy. Envy, an unpleasant emotion that stems from that desire to covet another's possessions, is often perceived as a negative outcome that should be banished to the deep recesses of a person's mind. However, recent research has determined that two forms of envy may exist, with positive outcomes for those experiencing benign envy. Often identified as "keeping up with the Joneses", feelings of benign envy may lead to motivating behavior, causing a person to strive to obtain what the other has in order to reduce their envy. In this dissertation, we seek to expand on the existing literature on benign envy, using construal level to determine the role concrete and abstract mental processing plays in feelings of benign envy and how this mindset affects willingness to purchase an item to relieve the envious feelings. In experiment 1, we find evidence that participants exposed to a concrete mental construal prime will be more likely to pay a price premium to obtain a product that is introduced to them by an envied person. Experiment 2 builds on the results of experiment 1, confirming the initial conclusions and finding evidence that those exposed to an envy-inducing situation are more likely to develop implementation intentions; that is, participants are more likely than those in the control condition (no envy) to determine exactly when and where they would purchase the item. Following a discussion of the results, managerial implications are presented, including how to induce a concrete mindset to an envious situation to increase the amount people will be willing to pay for an item, and how including information on where and when they can purchase the item could lead to a desire to pay more for a product that elicits feelings of envy.
Keywords: Construal Level Theory; Consumer Behavior; Envy